Methods of general stability calculation for flood embankment body and foundation - Asani, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the methods of general stability calculations for the body and foundation of the flood embankment and their applicability
Keywords: stateczność nasypu; obliczanie stateczności; wały przeciwpowodziowe; embankment stability; calculation of stability